2019
DOI: 10.1002/wnan.1582
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the size, shape and structure of RNA nanoparticles for favorable cancer targeting and immunostimulation

Abstract: The past decade has shown exponential growth in the field of RNA nanotechnology. The rapid advances of using RNA nanoparticles for biomedical applications, especially targeted cancer therapy, suggest its potential as a new generation of drug. After the first milestone of small molecule drugs and the second milestone of antibody drugs, it was predicted that RNA drugs, either RNA itself or chemicals/ligands that target RNA, will be the third milestone in drug development. Thus, a comprehensive assessment of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 125 publications
(275 reference statements)
0
36
0
Order By: Relevance
“…When immunoglobulin G (IgG), laminin, or complement proteins are adsorbed on the surface of NPs, specific uptake by immune cells is triggered, which may lead to immune stimulation response. 199 Studies showed that NPs first entered plasmacytoid-like dendritic cells through scavenger receptor-mediated endocytosis, and then the endosomal Toll-like receptors initiated IFN production, thereby generating an immunostimulatory response. 193,200 In addition to the intrinsic characters of NANPs, delivery systems may play an important role in immunological activity.…”
Section: Challenges Nanotoxicitymentioning
confidence: 99%
“…When immunoglobulin G (IgG), laminin, or complement proteins are adsorbed on the surface of NPs, specific uptake by immune cells is triggered, which may lead to immune stimulation response. 199 Studies showed that NPs first entered plasmacytoid-like dendritic cells through scavenger receptor-mediated endocytosis, and then the endosomal Toll-like receptors initiated IFN production, thereby generating an immunostimulatory response. 193,200 In addition to the intrinsic characters of NANPs, delivery systems may play an important role in immunological activity.…”
Section: Challenges Nanotoxicitymentioning
confidence: 99%
“…The numerous advantages of NPs—including delivery control, increased payload stability, and solubility, enhanced permeability, and retention, magnetic and optical properties—make them suitable vehicles to deliver a wide spectrum of molecular cargos [ 1 , 131 ]. However, physicochemical properties (i.e., size, shape, rigidity, or surface) profoundly influence the large-scale distribution of NPs and the ligand conjugation [ 132 , 133 , 134 , 135 , 136 ].…”
Section: Potentialities and Obstacles Of Anti-glycan Nps In Cancermentioning
confidence: 99%
“…Natural materials include chitosan, starch, alginate, cellulose, β-glucan yeast ghost particles or biosynthesized poly β-hydroxybutyrate. Synthetic materials include polyurethane, polylactic acid, poly (lactic-co-glycolic acid) (PLGA) and polymethyl methacrylate resins [ 60 , 174 , 175 , 176 , 177 , 178 ]. Especially natural materials have been extensively investigated for oral vaccine delivery due to their high biodegradability and compatibility, low to non-existing toxicity, strong adjuvanticity effects and their ability to retain the conformational structure of their loaded antigen [ 59 ].…”
Section: Oral Vaccination Strategiesmentioning
confidence: 99%